KIPRAHPONDOK PESANTREN MIFTAHUL ULUM BETTET PAMEKASAN DALAM MEWUJUDKAN PAMEKASAN SEBAGAI KOTA PENDIDIKAN - Atnawi, Atnawi (Universitas Islam Madura, 2017)
The implementation of boarding school activities at the education programs that is generally divided into two case both education – based boarding school and education-based schools, besides that, the education based school is also divided to formal education and non-formal education. For curriculum application, for the formal education curriculum is designed by using MORA while non-formal is designed of its own curriculum. The efforts have been made by Islamic Boarding School bettetPamekasan to face the District Education which including: 1) .Improving the educational boarding school programs maximally, both formal and non-formal education. 2). Emphasizing on the formation of behavior and characters more at the education programs. 3). Integrating Religion and public education in MiftahulUlum Islamic Boarding School. 4). Rejuvenating their education in different types of education at the boarding school. Thus, the expected results of this research can be input for the entire academic community in boarding school to face that Pamekasan is as an educational district primarily. In addition it is suggested that the implementation of education should be considered the development of student psychology, and the cost should also be considered, because there is existing BOS funds for the junior high school level, it is also an appreciation of the existence students or Islamic students have been more in the notice.